(untitled) (Journal of Contemporary Educational Policies and Practices, 2020)
English academic writing competences play such an integral part in students’ academic life. Nevertheless, students often deliver poor performances in academic writing class at university or have a great deal of difficulties in writing a composition. The paper presents the results from an action research project on the effectiveness of using scoring rubrics in teaching academic writing to English-majored freshmen in University of Languages and International Studies, Vietnam National University. 150 students coming from 6 different classes, all majoring in English language teaching or English language interpretation participated in this study. The article shows that after a semester using rubrics, the academic writing skills of students improved significantly with the increase in their grades also the decrease in the number of mistakes that they made during the writing process. However, there are still some certain hindrances to the use of rubrics in teaching and learning academic writing. Several recommendations are made concerning the effective use of scoring rubrics in academic writing class.